Safety last! - Roach, Hal 1892-1992; Whelan, Tim 1893-1957 (The Criterion collection, 2013)
The comic genius of silent star Harold Lloyd is eternal. He plays a small-town bumpkin trying to make it in the big city, who finds employment as a lowly department-store clerk. He comes up with a wild publicity stunt to draw attention to the store, resulting in an incredible feat of derring-do on his part that gets him started on the climb to success